PENGARUH KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU BERDAMPAK PADA MUTU LULUSAN - Anedi (DIALOGIKA, 2020)
This research is motivated by the phenomenon of low teacher performance which has an impact on the quality of graduates, presumably due to the low managerial ability of school principals and organizational culture. This study aims to determine: 1) the managerial ability of the principal; 2) organizational culture; 3) Teacher performance; 4) Quality of graduates; 5) The effect of principal managerial ability on teacher performance; 6) The influence of organizational culture on teacher performance; 7) The influence of principal managerial ability and organizational culture on teacher performance; 8) The effect of teacher performance on the quality of junior high school graduates in Majalengka Regency. Quantitative research methods with descriptive analysis techniques and verification. The descriptive method uses the calculation of frequency distribution, scoring and average value, while the verification method uses path analysis. The results of the descriptive study indicate that the principal's managerial abilities, organizational culture, teacher performance, and the quality of graduates are in good condition. The research results verificantly show that the principal managerial ability and organizational culture have a positive and significant effect on teacher performance either partially or simultaneously. Teacher performance has a positive and significant effect on the quality of graduates